Trypanocidal Activity of Flavokawin B, a Component of Polygonum ferrugineum Wedd - Rodrigues, Danilo F. [UNESP]; Maniscalco, David A.; Silva, Flavia A. J. [UNESP]; Chiari, Bruna G. [UNESP]; Castelli, Maria V.; Isaac, Vera L. B. [UNESP]; Cicarelli, Regina M. B. [UNESP]; Lopez, Silvia N. (Georg Thieme Verlag Kg, 2017)
The trypanocidal potential of the natural chalcone flavokawin B, which was isolated from the hexanic extract of Polygonum ferrugineum Wedd., is reported here. Although flavokawin B is widespread, this is the first report about its trypanocidal properties on both Trypanosoma cruzi (IC50 = 9.5 mu M, IC50 = 34.7 mu M benznidazol, Y strain) epimastigotes and Trypanosoma brucei (IC50 = 4.8 mu M, IC50 = 6.4 mu M pentamidine, 29-13 strain) procyclic forms, which was also corroborated on T. brucei strain 427 (IC50 = 6.2 mu M). In order to learn more about its properties, unspecific cytotoxicity on Hep G2 cells was investigated as well as the trans-splicing inhibitory potential on T. brucei cells. The results shown here point to flavokawin B as a candidate in the search for new agents. It is also cheaper and less toxic than the available drugs to treat trypanosomiasis with a special focus on sleeping sickness disease.
Keywords: Trypanosoma cruzi; Trypanosoma brucei; flavokawin B; chalcone; trans-splicing; Polygonum ferrugineum; Polygonaceae